Time to Act: Lessons Learnt from the First Pilot School-Based Intervention Study from Lebanon to Prevent and Reduce Childhood Obesity - Habib-Mourad, Carla; Ghandour, Lilian A. (Frontiers in Public Health, 2015)
Today, childhood overweight and obesity are serious public health problems facing the world. Obese children suffer from both short-term and long-term health consequences, and poorer adult health. Despite the rising prevalence of childhood obesity in the Eastern Mediterranean Region (EMR), including Lebanon, no intervention research studies have been undertaken. This paper summarizes the main challenges and lessons learned emanating from the first evidence-based multicomponent school intervention aimed at promoting Healthy Eating and Physical Activity in Lebanese School children (Health-E-PALS). Health-E-PALS, which includes three components (class curriculum, family involvement and food service) and relies on interactive fun learning activities, achieved an increase in students’ nutritional knowledge and self-efficacy, and a decrease in their purchase and consumption of high energy dense snacks and beverages. Recommendations for future school-based programs are also highlighted.